Contribution of Highly Qualified Employees to Regional Economy - Korshunov, Ilya A.; Shirkova, Natalia N.; Zavivaev, Nikolay S. (Economy of Regions, 2021)
Knowledge and skills concentrated in human capital are increasingly important factors of economic development. However, there is a lack of a methodology for determining, which skills are necessary for the efficient industrial development. To this end, we examine skill requirements of regional employers potentially leading to an increase in economic indicators. Skills in demand were compared with predicted indicators based on a semantic content analysis of vacancy databases in various regions of the Russian Federation. It was revealed that the list of demanded competencies depends not on a geographical aspect but on a specific profession. An analysis of the obtained data demonstrated that the growth in demand for highly qualified employees in the Russian Federation is correlated with an increase in gross value added of relevant industries. A linear correlation between gross value added per employee and the need for skilled specialists was demonstrated on the example of the transport sector. The proposed methodology can be used by educational organisations for targeted training of specialists, as well as by employers and experts for forecasting medium- and long-term socio-economic development of Russian regions.